Metabolic syndrome, neurohumoral modulation, and pulmonary arterial hypertension - Maron, Bradley A. (Br J Pharmacol, 2020)
Pulmonary vascular disease, including pulmonary arterial hypertension (PAH), is increasingly recognized to be affected by systemic alterations including up‐regulation of the renin‐angiotensin‐aldosterone system and perturbations to metabolic pathways, particularly glucose and fat metabolism. There is increasing preclinical and clinical data that each of these pathways can promote pulmonary vascular disease and right heart failure and are not simply disease markers. More recently, trials of therapeutics aimed at neurohormonal activation or metabolic dysfunction are beginning to shed light on how interventions in these pathways may affect patients with PAH. This review will focus on underlying mechanistic data that supports neurohormonal activation and metabolic dysfunction in the pathogenesis of PAH and right heart failure as well as discussing early translational data in patients with PAH.